Cryptococcal meningitis - a follow-up study of a serious clinical entity: quick cytological and microbiological diagnostics using a special staining procedure in cerebrospinal fluid specimens - Adam, Pavel; Sobek, Ondřej; Doležil, David; Lodin, Zdeněk; Kasík, Jiří; Hajduková, Lenka; Cihelková, Š; Svatoňová, Jana; Hybeľová, Mária; Adam, David; Melezinková, Veronika (Folia microbiologica, 2009)
A routine diagnostic procedure of cryptococcal meningitis using Alcian Blue and Nuclear Fast Red staining is described in a group of 16 patients. Cerebrospinal fluid findings, including clinical cytology, routine biochemistry and protein fractions, are presented.
Keywords: Cerebrospinal Fluid; Meningitis, Cryptococcal; Humans; Microscopy; mozkomíšní mok; Cryptococcus neoformans; lidé; kryptokoková meningitida; Microbiological Techniques; mikrobiologické techniky; mikroskopie; Staining and Labeling; barvení a značení